Towards a sustainable global food system: what will it take? - Pinstrup-Andersen, Per (2002)
Past successes in food production have resulted in significant increases in per capita food availability. Global food supplies per person are greater today than ever before. In fact, current global food supplies are sufficient to meet nutritional requirements of all people, if the food were distributed according to needs... The challenge confronting us is to continue the expansion of food production to meet future demand without negative effects on the environment. The other major food-related challenge is to assure that everyone has access to sufficient food to live a healthy and productive life. To meet these two challenges, policies and technologies must be designed and implemented that will eliminate food insecurity, hunger, and malnutrition in a manner consistent with an ecologically sustainable management of natural resources." -- from Introduction.